Kierkegaard's Journals and Notebooks, Volume 3 : Notebooks 1-15 - Kierkegaard, Soren, 1813-1855 (Book collections on Project MUSE., 2010)
Soren Kierkegaard (1813-55) published an extraordinary number of works during his lifetime, but he left behind nearly as much unpublished writing, most of which consists of what are called his ""journals and notebooks."" Volume 3 of this 11-volume edition of Kierkegaard's Journals and Notebooks includes Kierkegaard's extensive notes on lectures by the Danish theologian H.N. Clausen and by the German philosopher Schelling, as well as a great many other entries on philosophical, theological, and literary topics. In addition, the volume includes many personal reflections by Kierkegaard.